Grounding cosmopolitanism : from Kant to the idea of a cosmopolitan constitution - Brown, Garrett Wallace (Edinburgh University Press, 2009)
This book explores Kant's cosmopolitanism and the normative requirements consistent with a Kantian based cosmopolitan constitution. Topics such as cosmopolitan law, cosmopolitan right, the laws of hospitality, a Kantian federation of states, a cosmopolitan epistemology of culture and a possible normative basis for a Kantian form of global distributive justice are explored and defended. Contrary to many contemporary interpretations, Brown considers Kant's cosmopolitan thought as a form of international constitutional jurisprudence that requires minimal legal demands versus the extreme condition of establishing a world state. Viewing Kant's cosmopolitan theory as a minimal form of global jurisprudence allows it to satisfy communitarian, realist and pluralist concerns without surrendering cosmopolitan principles of human worth and cosmopolitan law. In this regard, it provides a more comprehensive understanding of Kantian cosmopolitanism and what normative implications this vision has for contemporary international political theory. Key Features. Outlines the various positions within Kant's cosmopolitanism and examines their interrelated themes and conclusions Defends a Kantian cosmopolitan position against its most profound critics Argues for the contemporary and interdisciplinary relevance of Kant's cosmopolitan thought and its importance for understanding and resolving current global concerns